Borrower protection and the supply of credit: Evidence from foreclosure laws - Dagher, Jihad; Sun, Yangfan (Journal of Financial Economics, 2016)
Laws governing the foreclosure process can have direct consequences for the costs of foreclosure and, therefore could affect lending decisions. We exploit the heterogeneity in judicial requirements across US states to examine their impact on banks’ lending decisions in a sample of urban areas straddling state borders. A key feature of our study is the way it exploits an exogenous cutoff in loan eligibility to government-sponsored enterprises (GSEs) guarantees, which shift the burden of foreclosure costs onto the GSEs. We find that judicial requirements reduce the supply of credit only for jumbo loans, which are ineligible for GSE guarantees, i.e., in the nonsubsidized segment of the market. Thus, while we find a significant effect on credit supply, the aggregate impact is muted by the indirect cross-subsidy by the GSEs to borrower-friendly states.